One and Two‐Photon Excited Fluorescence Optimization of Metal–Organic Frameworks with Symmetry‐Reduced AIEgen‐Ligand. (20th September 2022) - Wang, Shi‐Cheng; Zhang, Qiang‐Sheng; Wang, Zheng; Zheng, Lin; Zhang, Xiao‐Dong; Fan, Ya‐Nan; Fu, Peng‐Yan; Xiong, Xiao‐Hong; Pan, Mei
Abstract: By designing a tetraphenylethylene (TPE)‐based AIEgen‐ligand with reduced symmetry, we obtained two alkaline‐earth metal‐based MOFs (LIFM‐102 and LIFM‐103) with dense packing structures and low porosity as proved by single‐crystal X‐ray diffraction and CO2 sorption data. Excitingly, the desolvated MOFs with rigid environment and reduced lattice free solvent exhibit high quantum yields (QY, 64.9 % and 79.4 %) and excellent two‐photon excited photoluminescence (TPA cross‐sections, 2946.6 GM and 2899.0 GM), while maintaining the external‐stimuli‐responsive properties suitable for anticounterfeit fields. The effect of ligand conformation was validated by comparing the structure and fluorescence properties of the samples before and after desolvation and further verified by theoretical calculations. This work expands the study on TPE‐cored materials to symmetry‐reduced ligand and might bring forward novel structures and excellent photoluminescent properties in the future. Abstract : A symmetry‐reduced TPE‐cored ligand was applied for the construction of MOFs with dense packing structures, which are beneficial to the improvement of one‐ and two‐photon excited fluorescent properties, achieving high TPA cross‐sections of ≈3000 GM.